Creating and shaping the DHM tool IMMA for ergonomic product and production design. (2016) - Högberg, Dan; Hanson, Lars; Bohlin, Robert; Carlson, Johan S.
The history, status and outlook of the research and development actions associated with the creation of the digital human modelling tool intelligently moving manikins (IMMA) are described. The underlying fundamental concepts are described and research and development results so far are illustrated or referred to. Two case studies illustrating use of IMMA on industry-based problems are described. The paper also covers reflections on conceptions for prospective DHM tool developments from a general perspective, relating to areas of ergonomics and design methodology, as well as describing some of the plans for further developments and applications of the IMMA tool. These may be of assistance when identifying challenges for future research and development of DHM tools that are used in product and production design processes in industry.